مساهمة نظام إدارة الجودة الإيزو 9001 - 2000 في تحسين الأداء بالمؤسسة: دراسة حالة مؤسسة EN.I.CA.B بسكرة - خير الدين، جمعة Khairuldin, Jumaah (جامعة محمد خيضر بسكرة, 2016)
This study aims to find out the contribution of the Quality Management System ISO 2000: 9001 to improve the performance of the organization (EN.I.CA.B) Biskra, as struggling institutions seeking to raise their performance through several entrances, including ISO 2000: 9001 system, because of its a significant role in the development of rules and standards that work to unify the requirements of commercial competition among the various institutions, the study found that the quality management system "ISO 9001: 2000" constitutes a competitive advantage, trying to absorb the institution the largest possible share of the market
تهدف هذه الدراسة إلى معرفة مساهمة نظام إدارة الجودة الأيزو 2000:9001 في تحسين الأداء ببسكرة، إذ (EN.I.CA.B) بمؤسسة تسعى المؤسسات جاهدة إلى رفع أدائها من خلال عدة مداخل، من بينها نظام الأيزو2000:9001 ، لما له من دور كبير في وضع القواعد والمقاييس التي تعمل على توحيد متطلبات المنافسة التجارية بين مختلف المؤسسات، وتوصلت الدراسة إلى أن نظام إدارة الجودة “الايزو 2000:9001 " يشكل ميزة تنافسية تحاول من خلالها المؤسسة استيعاب أكبر حصة ممكنة من السوق.
Keywords: السياسة الإقتصادية -- التنمية الإقتصادية -- النمو الإقتصادي -- التنمية المستدامة -- الاداء الوظيفي -- المؤسسات الإقتصادية -- نظام إدارة الجودة الشاملة -- الجزائر -- المجتمع الجزائري -- مستخلصات الأبحاث